Barriers and facilitators in the acquisition of diabetes knowledge among tertiary-care nurses in central and southern Malawi: an exploratory-descriptive qualitative study - McDonald William Nyalapa; Belinda Thandizo Gombachika; Rodwell Gundo; Lignet Chepuka (BMC Health Services Research)
Abstract Background Numerous studies report low diabetes knowledge among nurses in sub-Saharan Africa. However, little is known about the factors that hinder and promote their acquisition of knowledge on diabetes mellitus. Understanding these factors is a pivotal step towards ensuring that nurses are knowledgeable and competent in the provision of care and education for patients with diabetes mellitus. Methods The study employed an exploratory-descriptive qualitative (EDQ) approach. Participants were identified from two tertiary hospitals. Twenty-six participants were purposively selected from these facilities. Data were collected through focus group discussions and analysis was done using Braun and Clarke’s approach to thematic analysis. Results The following themes relating to barriers and facilitators in the nurses’ acquisition of diabetes knowledge emerged from the study: (a) individual hindrances; (b) organizational drawbacks; (c) personal ways of knowing; (d) organizational factors enhancing knowledge; and (e) suggestions for improving the nurses’ knowledge. Conclusions The study brings to light various challenges and opportunities in the acquisition of diabetes knowledge among tertiary-care nurses in Malawi. Given our study results, we believe that cost-effective measures can be utilised to address the barriers to the acquisition of diabetes knowledge among nurses. This is a crucial step towards ensuring that nurses are knowledgeable and competent in the provision of care for patients with diabetes in low-resource countries.